Pengaruh Konsentrasi Grafena Oksida Dan Curing Temperature Pada Sintesis Mortar Geopolimer Berbasis Limbah Palm Oil Fly Ash (POFA) - Najib, Ahmad Ainun; Amri, Amun; Olivia, Monita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This research aims to study the effects of graphene oxide addition and curing temperature toward the compressive strength of Palm Oil Fly Ash (POFA) based geopolymer. Matrixes were prepared by mixing treated palm oil fly ash and fine aggregate and continued by preparing alkali activator of 10 M sodium hydroxide and 33,3 mL sodium silicate also different concentration of graphene oxide (0 mg/mL, 1 mg/mL and 3 mg/mL) were mixed for 1 hour. Solid and liquid were mixed together with ratio 0,39 and placed them in geopolymer mortar mold (50 mm x 50 mm x 50 mm) which were cured at room temperature for 1 hour and heated them in oven for 24 hours at different temperature (40oC, 60oC and 80oC). The highest compressive strength was 11.4MPa yielded by adding 3mg/mL of graphene oxide at 80oC.Keywords: compressive strength, curing temperature, geopolymer, graphene oxide, palm oil fly ash